President’s Message - Knight, Mary (Operating Room Nurses Association of Canada Journal, 2003)
The theme chosen for the 2002 Perioperative Nurses' Week "Perioperative Registered Nurses: Ensuring Patient Safety" was chosen because since the beginning of surgery as we know it, nursing activities within the perioperative setting have promoted safety foro the surgical patient. Through verification of our patient's identity and surgical site, surgical asepsis, infection control practices, environmental safety, surgical counts, documentation, etc., we have integrated the core value of patient safety into our everyday practice in a high-tech and incredibly complex environment. Patient safety has always been, and will continue to be, our primary raison d'être.